Assessment of lead tolerance on Glycine max (L.) Merr. at early growth stages - Blanco, Andrés (2021)
Lead (Pb) contamination of agricultural soils, and subsequently of crops, has been widely reported. Soybean (Glycine max (L.) Merr.) has been indicated as a plant that accumulates Pb, even in soils that do not exceed the maximum permissible levels. Considering the toxicity of this heavy metal, the aim of the present study was to assess different concentrations of Pb, from low to extremely high (0.25 mM, 1 mM, and 2.5 mM), in soybean seedlings and their tolerance by analyzing morpho-physiological parameters in hydroponic experiments. Soybean seedlings were exposed to control and Pb treatments during 8 days, coinciding with the early growth stages, and the following variables were analyzed: biomass, Pb content in roots, stems and leaves, photosynthetic efficiency, leaf area, biochemical response (antioxidant power, chlorophylls, malondialdehyde), and relative water content of leaves. Results showed that roots accumulated much more Pb than the other organs, with Pb accumulation in roots being saturated even at the lowest Pb concentration, which was reflected in root biomass. Moreover, absorption of culture solutions was lower in Pb treatments, which was also reflected in the lower leaf relative water content. Lead toxicity symptoms in leaves (chlorosis and dark spots, and a decrease of biomass and leaf area, chlorophyll content, and photosynthetic efficiency), and an increase of the oxidative defense system were associated only with the highest Pb concentration (2.5 mM). Our findings support the evidence of soybean as a species tolerant to Pb, showing the effects of toxicity at very high concentrations.